2021
DOI: 10.1111/bjdp.12372
|View full text |Cite
|
Sign up to set email alerts
|

Lebanese adolescents’ expectations about social inclusion of peers in intergroup contexts

Abstract: This study examined the role of group norms, group identity, age, contact, and stereotypes on youths’ decisions to include a peer in an intergroup context portraying Lebanese and American adolescents. Lebanese participants (N = 275), ages 12 and 16 years, were surveyed about expectations for inclusion of an out‐group target with similar interests or an in‐group target with different interests into their own Lebanese group or another American group. Findings indicated participants focused on shared interests, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In light of this more recent research and from an SRD perspective, we expected Lebanese youth would approve of inclusive deviants and disapprove of exclusive deviants. While inter‐cultural inclusivity of Lebanese adolescents was demonstrated in previous research, expectations for outgroup inclusivity varied by age, indicating that older adolescents expected an American outgroup to be less inclusive than younger adolescents (Hitti et al, 2021). This indicated an expectation for bias among American outgroup peers.…”
Section: Studymentioning
confidence: 81%
See 2 more Smart Citations
“…In light of this more recent research and from an SRD perspective, we expected Lebanese youth would approve of inclusive deviants and disapprove of exclusive deviants. While inter‐cultural inclusivity of Lebanese adolescents was demonstrated in previous research, expectations for outgroup inclusivity varied by age, indicating that older adolescents expected an American outgroup to be less inclusive than younger adolescents (Hitti et al, 2021). This indicated an expectation for bias among American outgroup peers.…”
Section: Studymentioning
confidence: 81%
“…Past intergroup research focused on racial or ethnic inclusion and exclusion in predominantly European and North American samples. Recently, a study with Lebanese Arab adolescents, an under‐represented population in developmental and social psychology research, evidenced inter‐cultural inclusivity in a Lebanese/American intergroup context (Hitti et al, 2021). However, less is known about whether Lebanese youth value those who stand up to injustices such as inter‐cultural exclusion.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in longitudinal studies initial perceptions of peer group inclusivity affected later interest in, comfort with, and quality of cross‐ethnic friendships (Tropp et al, 2016), as well as attitudes about contact (Rivas‐Drake et al, 2019). The extent to which adolescents perceive their peers to be inclusive toward immigrants predicts attitudes and behaviors toward immigrant‐origin peers (Gönültaş & Mulvey, 2021; Hitti et al, 2021). Similarly, in a study in Northern Ireland (McKeown & Taylor, 2018), it was demonstrated that inclusive peer norms increased one's willingness to engage in prosocial behaviors with an outgroup member, but contact experiences with outgroups were driving this willingness to help an outgroup.…”
Section: Introductionmentioning
confidence: 99%